2020
DOI: 10.5005/jp-journals-10024-2753
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Impact of Acidic Drink on the Microhardness of Different Esthetic Restorative Materials: An In Vitro Study

Abstract: Aim:The aim of this study was to assess the impact of acidic drink on the microhardness of different esthetic restorative materials. Materials and methods: Sixty samples (20 samples of each group) were prepared. group I: nanohybrid ormocer-based composite, group II: glasiosite compomer, and group III: nanoceramic composite. A cylindrical aluminum mold of 5 mm depth and 10 mm internal diameter was used to prepare the samples. All the esthetic restorative samples were submerged in 25 mL of acidic drink (Coca-Col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The change in surface microhardness was less obvious in Admira fusion in most tested groups which is in agreement with Moyin et al [ 9 ]. This could be attributed to the nature of Admira fusion, being an ormocer.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The change in surface microhardness was less obvious in Admira fusion in most tested groups which is in agreement with Moyin et al [ 9 ]. This could be attributed to the nature of Admira fusion, being an ormocer.…”
Section: Discussionsupporting
confidence: 91%
“…The popularity of different beverages with high acidic or alcoholic content has raised questions about their degradative potential [ 8 ]. Acidic and alcoholic content present in different beverages can cause a reduction in the surface microhardness of composites by softening the bis-GMA based polymers present in the organic matrix [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Namely, the study by Borges et al reported that 30-day cyclic immersion in acidic drinks diminished MH of composites to the following extents: juice 3–18%, red wine 4–20%, and Coca-Cola 9–22% [ 13 ]. Another study showed that Coca-Cola immersion for 15 days decreased MH of resin composites and compomers by 13–22% [ 14 ]. Additionally, 1-month immersion in multivitamin syrups and effervescent tablets was shown to diminish MH values by 21–28% for a resin composite, and 13–35% for a glass hybrid [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…These conditions cause a gradual degradation of mechanical and chemical properties, consequently affecting the service life of dental restorations [ 10 ]. A number of previous studies have shown that acidic dietary foods and beverages can cause surface degradation for various types of dental restorative materials [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Concurrently with the increasing consumption of soft and fruit drinks, their potential for damaging dental hard tissues and restorative materials is becoming an important factor affecting the lifespan of contemporary dental restorations [ 21 ].…”
Section: Introductionmentioning
confidence: 99%